Long-distance hiking lessons from the Appalachian Trail - Mueser, Roland (Ragged Mountain Press, 1998)
Intended for those considering a long-distance trek, this is a guide to long-distance backpacking. It offers responses to questions, such as: which brand of backpack do most long distance hikers prefer? How much money will I need? Is a walking stick an advantage or a nuisance? What percentage of hikers wear underwear? And more.